THE PRINCIPLES OF ISLAMIC EDUCATION MANAGEMENT IN SHAPING NOBLE CHARACTER FROM THE PERSPECTIVE OF SURAH AL-AHZAB 33:70 - Yaqin, Mohammad Nurul; Sumedi, Sumedi (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
Islamic education management requires continuous innovation to stay relevant and beneficial. This system relies on the Qur'an and Hadith to guide individuals towards a better life in this world and the Hereafter. Key principles include integration, balance, universality, and dynamism. This study explores these principles in shaping noble character through Surah Al-Ahzab 33:70, using textual and contextual analysis. It draws from primary data in the Qur'an and secondary sources like tafsir books. The findings show that Islamic education management principles influence behavior towards God, oneself, others, and the environment, emphasizing honesty to foster progress and contribute to effective planning.